The Influence of Sport Representation and Attitudes Toward Strength Training on Neuromuscular Performance Profiles in University Athletes: Part I Female Athletes. - McClean, Zachary J.; da Silva Torres, Ricardo; Herzog, Walter; Pasanen, Kati; Lun, Victor; Nimphius, Sophia; Jordan, Matthew J. (Journal of Strength & Conditioning Research, 2026)
McClean, ZJ, da Silva Torres, R, Herzog, W, Pasanen, K, Lun, V, Nimphius, S, and Jordan, MJ. The influence of sport representation and attitudes toward strength training on neuromuscular performance profiles in university athletes: part I female athletes. J Strength Cond Res 40(3): 311–323, 2026—Neuromuscular performance is often assessed across strength, power, and plyometric tasks in athlete populations with an increasing emphasis on biomechanical testing that yields multifaceted data sets with several outcome measures per task. This leads to specific challenges in determining relevant neuromuscular performance benchmarks especially when considering contextual factors related to the sport environment. Thus, characterizing athlete neuromuscular performance subpopulations (or profiles) while accounting for the influence of contextual factors such as those related to the sport environment, and psychosocial factors such as the athlete's attitudes toward strength training could provide a framework for more specific neuromuscular benchmarks. Therefore, neuromuscular performance profiles were explored in female university athletes while accounting for sport influences and attitudes toward strength training. Female university athletes (n = 192) from 5 sports completed a comprehensive lower body neuromuscular performance testing battery and surveys assessing attitudes toward strength training. Clustering was done to define neuromuscular performance profiles and Fisher's Exact Tests were used to examine differences in attitudes toward strength training across clusters. A high-strength/high-power/high-stiffness cluster, low-strength/low-power/low-stiffness cluster, and low-strength/low-power/high-stiffness cluster were identified with no difference in sport representation but differences in attitudes toward strength training (p < 0.047; alpha = 0.05). These findings may help to quantify the characteristics of different female university athlete neuromuscular performance profiles while accounting for potential sport and psychosocial influences. One potential application of these results is to inform neuromuscular performance benchmarks that can be used in conjunction with preseason evaluations or in the context of restoring performance readiness after injury.